The Golden Age of the Abbasids: Arabic Language and Literature as Pillars of Progress - Winarno, Raysa Kaila Azzah; Renata, Dea Zahira Berliana; Habibah, Cavita; Hasaniyah, Nur Hasaniyah (Merwin Publisher, 2025)
The golden age of the Abbasid Dynasty (750–1258 CE) was a crucial phase in the history of Islamic civilization, marked by rapid advances in science, education, and culture. The caliphs, particularly Harun al-Rashid and Al-Ma'mun, played a significant role in promoting scientific activity through the establishment of institutions such as the Baitul Hikmah, which served as centers for translation, libraries, and scientific development. Arabic developed into the primary language of science, replacing Greek and Syriac, and became a medium for the transmission and innovation of knowledge from various civilizations, such as Greece, Persia, and India. This study aims to analyze the role of Arabic language and literature as the main pillars of the progress of Islamic civilization during the Abbasid Dynasty. The method used is a qualitative approach with a descriptive-analytical design through a literature study of relevant primary and secondary sources. The results show that Arabic not only functions as a means of communication, but also as a primary means of developing and producing knowledge, while Arabic literature developed rapidly through cross-cultural interactions and political support from the Caliphate. These findings confirm that intellectual progress during the Abbasid period significantly contributed to the development of global science and laid the foundation for modern civilization.